The Analysis Of Stenberg's Triangle Love Theory On Early Adult Couples Of Ba'lawi Arab Descent Who Experienced Arranged Marriages - Naziha Syihab; Aisyah Syihab; Sri Juwita Kusumawardhani (Psikis : Jurnal Psikologi Islami, 2021)
This study aims to determine the distribution of types of love based on Stenberg's Triangle Love Theory in primary adult of Ba'alawi Arab descent couples in Jakarta who experienced an arranged marriage. This study uses a quantitative descriptive method with descriptive statistical analysis. The measuring instrument used is the Triangular of Love Scale (TLS) to measure the type of love and the Arranged Marriage Questionnaire (AMQ) to see attitudes in selecting a partner for marriage. Respondents in this study were 154 people, with the sample characteristics being early adults aged 21-40 years, experiencing arranged marriages, married with a marriage age range of 0-10 years, and the last education was at least high school, and lived in Jakarta. The results of this study indicate that the distribution of the type of love that respondents have is more dominant in non-love (53.9%), consummate love (22.1%), and empty love (11%). In this study, it is understandable that respondents prefer to marry in a way that tends not in an arranged marriage (56.5%).